Geber Madu Ayu, Gerakan Bersama Memajukan Pos Pelayanan Terpadu (Posyandu) di Kabupaten Indramayu - Indra Ruswadi; Nengsih Yulianingsih; Hasim Asyari; Masliha Masliha (Pusat Riset dan Inovasi Nasional, 2022)
The Integrated Service Post, known as Posyandu, is the front line in health services and other multifunctional services. However, at this time its existence has not been seen optimally, this is due to the lack of Posyandu implementers and managers in understanding the existence of Posyandu, so that reports on Posyandu activities that should be carried out in stages have not been carried out optimally, besides that there is still an assumption that Posyandu belongs to Health people. The objectives of the service activities are: Understanding Geber Madu Ayu, Joint Movement for Advancing Posyandu in Indramayu Regency. Methods: lectures, discussions and simulations. The results of the activity: All management of the Posyandu, Village Working Group, District Pokjanal and District Posyandu Pokjanal understand the importance of the Joint Movement to Promote Integrated Service Posts (Posyandu) in Indramayu Regency. Conclusion: The Joint Movement to establish a posyandu in Indramayu has been received and received a good response from stakeholders. Suggestion: Posyandu administrators at every level should increase their commitment to advancing posyandu by involving related elements, ranging from academics, business people, communities and media as well as advocating for regional/government heads.